The Effect of Conducting Practical Hand-On Activities in SMK Negeri 4 Muko-Muko - Siska, Jumiati; Franzhardi, Didi (CV Media Inti Teknologi, 2025)
Background of study: The Fourth Industrial Revolution demands graduates equipped with practical, adaptive skills beyond theoretical knowledge. However, conventional teacher-centered instruction often hinders the development of essential competencies, especially in vocational subjects such as graphic design using CorelDRAW, where direct practice is crucial. Aims and scope of paper: This study aims to examine the effectiveness of the Hands-On Activity learning model in improving learning outcomes, motivation, and technical skills of grade X Multimedia students at SMK Negeri 4 Mukomuko. Methods: A quantitative quasi-experimental method was employed using a Nonequivalent Control Group Design involving two naturally formed classes of 30 students each. Class X Multimedia A was assigned as the experimental group (Hands-On Activity), and Class X Multimedia B as the control group (conventional learning). Data were collected through validated pretest and posttest instruments. Normality was tested using Shapiro-Wilk, and homogeneity using Levene's test. An independent samples t-test was conducted to determine the effect of the treatment. Result: The results showed a significant improvement in the experimental group’s learning outcomes. The normality test confirmed the data were normally distributed (Sig. > 0.05), and the homogeneity test indicated equal variances (p = 0.125). Hypothesis testing revealed a t-value of 10.57, exceeding the critical value of 2.0024, leading to the acceptance of the alternative hypothesis. Conclusion: The study concludes that the Hands-On Activity model effectively enhances student engagement, motivation, and mastery of both theoretical and practical knowledge in Informatics, making it a suitable strategy for vocational education.